Collaborative Opportunity: Growing a Community around Integrated Engineering - Bates, Rebecca; Tilley, Emanuela; Carpenter, Jenna; Lord, Susan (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Integrated Engineering is emerging across the world. One commonality among programs is a desire to innovate in ways not seen as possible within traditional engineering disciplines. The inclusive pedagogical approaches seen in integrated engineering programs offer promise for truly transforming engineering education. These student-centered approaches align with caring pedagogies and provide sustainable infrastructure for supporting diverse student experiences. Innovation in engineering education can be challenging to implement and can be challenging to sustain. Community support can make a positive difference. Building on a series of community conversations at multiple international conferences as well as an international symposium in London during the summer of 2024, this paper will be used to spark a conversation about innovations related to integrated engineering. The goal is to include new voices to extend the existing community, build a stronger network, and provide an opportunity to reflect and plan implementation steps for enacting holistic approaches to engineering education.